USING EXTENSIVE READING TO IMPROVE THE STUDENTS’ ABILITY IN READING COMPREHENSION AT MAN 1 BIREUEN IN ACADEMIC YEAR 2020/2021 - FAZZILLAH; MUHAMMAD AFRIZAL (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2022)
The title of this thesis is Using Extensive Reading to improve the students’ Ability in reading comprehension at MAN I Bireuen in academic year 2020/2021(A Collaborative Classroom Action Research). From the title above, the researcher found some problem from the students, the students had got less information, the students did not know the main ideas in paragraph, the students had difficulty to comprehend the text they read. So, the researcher put three problems of this research with the questions as follow: first, how can Extensive Reading improve the students’ ability in reading comprehension? Second, how do the students respond toward the implementation of extensive reading in improving students’ ability in reading comprehention. Three, how is the implementation of extensive reading in improving students ability in reading comprehension? Based on the research problems, the purpose of this research were: first, to know the improvement students’ ability in reading comprehension through Extensive Reading. Second, to find out the process of the implementation of Extensive Reading in reading comprehention. And the three, to know the students respond toward the implementation of Extensive Reading. This research was a collaborative classroom action research that was done in two cycles. The research was a collaborative classroom action research that was done in two cycles. The research sample of this research was 20 students. The data was collected through the field note, reading test, students’ observation checklist, the teacher’s observation checklist, and questionnaire. The data was analyzed through the descriptive qualitative research. The research was conducted into two cycles, the procedure of action research: planning, implementing, observing, and reflecting. The first cycle consisted of third meetings, and the second cycle consisted of two meetings. After the researcher was done all the steps of action research (cycle 1 and cycle 2) the students’ means increased from 53 in cycle 1 became 78 in cycle II. The finding of the research also showed that Extensive Reading can improve the students’ reading narrative text, it was showed from the result of students’ mastery reading test in each cycle which the action implemented.